Peer Tutoring on Fish and Vegetables-Based Diet Education to Prevent Anemia and Hypoalbuminemia in Adolescents - Annasari Mustafa; Endang Widajati; Farida Halis; Khairuddin Khairuddin (Indonesian Journal of Human Nutrition, 2023)
Early detection of nutritional problems is a vital skill for individuals as it enables timely prevention before any symptoms arise. This skill can be fostered through enhancing knowledge, practicing skills via educational activities and mentoring, and seeking support from peers who share similar challenges. This study aims to investigate the impact of peer tutoring on the development of a balanced menu and healthy snack consumption based on fish and vegetables among 11th-grade female students at a state high school in Singosari, Malang Regency. This study examined the effect of these interventions on the intake of energy, protein, and iron among the participants. Data were gathered by collecting food consumption data using the 24-hour food recall method and measurement of weight, height, Hb, and Albumin levels. The study employed a purposive sampling technique by conducting pretest, intervention, and post-test. The results showed significant improvements in the health indicators of the participants, including knowledge, intake, Hb, and Albumin levels (p=0.000; α=0.005). These findings demonstrate the potential of education and mentoring through peer tutoring in promoting healthy eating habits and preventing nutrition-related problems among female adolescents.